Setting Forth a Canon of the Gurdjieff Work. Issue 2 (1st February 2022) - Seamon, David
Abstract : This article considers whether there might be a canon of the Gurdjieff Work and, if so, what that canon might include. The author emphasizes that any canonical explication must incorporate two complementary aspects: first, texts that describe the psychological, philosophical, metaphysical, and cosmological structure of Gurdjieff's system of self-transformation; second, an integrated set of guidelines, procedures, and techniques that provide the experiential and spiritual engine for actualizing potential self-transformation. Taking this twofold canonical definition into account, the Gurdjieff canon is defined as an ensemble of texts, methods, and performative media that when, engaged sincerely and persistently, might facilitate self-transformation psychologically and spiritually. This article gives attention to written texts because the starting point of Gurdjieff's system is intellectual understanding. These written texts are overviewed in terms of seven categories: (1) Gurdjieff's Beelzebub's Tales to His Grandson and Ouspensky's In Search of the Miraculous; (2) additional texts by Gurdjieff and Ouspensky, including Gurdjieff's Meetings with Remarkable Men and Ouspensky's The Fourth Way; (3) commentaries on Beelzebub's Tales; (4) commentaries on the Gurdjieff Work as presented in Maurice Nicoll's Psychological Commentaries and Jane Heap's Notebooks; (5) biographies of Gurdjieff; (6) memoirs of Gurdjieff; and (7) works that extend Gurdjieffian ideas in innovative directions.